Gender stereotypes and professional experiences of female nurses in Türkiye - Zeynep Aca; Arzu Kırcal-Şahin; Akın Özdemir; Yavuz Selim Kaymakcı (Frontiers in Public Health)
IntroductionGender roles and stereotypes play a significant role in shaping the nursing profession, perpetuating systemic inequities that negatively impact professional experiences and healthcare system efficiency. In Türkiye, patriarchal norms and systemic disparities exacerbate these workplace challenges, particularly for female nurses.MethodsThis qualitative study utilized semi-structured interviews with 13 female nurses working in intensive care units to examine the influence of societal expectations, workplace discrimination, and institutional policies on gender inequities in nursing.ResultsThe findings reveal that cultural norms, family influence, and constrained career planning often channel women into nursing, reinforcing perceptions of the profession as an extension of caregiving roles. While participants rejected the notion of nursing as a “women’s profession,” their narratives highlighted the pervasive impact of gendered expectations. Additionally, political favoritism and nepotism were identified as factors exacerbating workplace challenges, reflecting broader systemic issues in Türkiye’s labor market. The normalization of gender norms and their internalization by female nurses further complicate efforts to combat discrimination.DiscussionThe study underscores the necessity for policy interventions to address systemic gender inequities in nursing. Recommendations include implementing mandatory gender equality education within healthcare institutions, stricter enforcement of anti-violence laws, and the establishment of psychological and legal support systems for workplace violence victims. Additional measures, such as childcare support and regulations against marital status-based discrimination, are essential to mitigate inequities. By addressing societal, cultural, and institutional factors, this research provides actionable strategies for healthcare organizations and policymakers to promote equity and improve sector efficiency.